Optimalisasi Media Sosial Facebook Sebagai Penunjang Digital Marketing Pada PT Sreeya Sewu Indonesia, Tbk - Dewi Fathika Sari; Nurjanti Takarini (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Digital Marketing is a strategy that will help in increasing brand awareness for consumers. Indonesia, Tbk. The implementation of social media optimization within the company, it involves interns from Certified Independent Study Interns (MSIB) who will later be equipped with knowledge about Digital Marketing and there are also stages in the application of Digital Marketing starting from pre-preparation, content preparation, optimization implementation. social media Facebook, and Evaluation. The purpose of this activity is to prepare students who are ready to work with sufficient experience in the field of Digital Marketing assisted by PT. Sreeya Sewu Indonesia, Tbk. In the internship activities carried out by marketing, there are applications to support the optimization of Facebook's social media, namely utilizing the Meta Business Suite feature. Meta Business Suite is an application that businesses use in content management, scheduling posts, managing ads, and viewing insights. With this activity, the company's Facebook social media account PT. Sreeya Sewu Indonesia, Tbk experienced an increase in reach of 9.0% thousand, page views and profiles increased by 129.6%, and likes and follows only increased by 56.3%.